2005
DOI: 10.1016/j.bbamcr.2005.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence methods to detect phase boundaries in lipid bilayer mixtures

Abstract: Phase diagrams of lipid mixtures can show several different regions of phase coexistence, which include liquid-disordered, liquid-ordered, and gel phases. Some phase regions are small, and some have sharp boundaries. The identity of the phases, their location in composition space, and the nature of the transitions between the phases are important for understanding the behavior of lipid mixtures. High fidelity phase boundary detection requires high compositional resolution, on the order of 2% compositional incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 18 publications
1
68
1
Order By: Relevance
“…While the exact size and shape of domains in our SLB studies of this lipid mixture was difficult to control between experiments, the same general membrane morphology (two-phase co-existence, domains in registry) was consistent. The fluorescent probe DiI-C 20 has been shown to preferentially partition into solid-ordered (S o ) gel and L o membrane phases (Baumgart et al, 2007;Feigenson and Buboltz, 2001;Hao et al, 2001;Heberle et al, 2005;Korlach et al, 1999;Spink et al, 1990). Indeed, we observed that the probe showed a preference for one of the membrane phases; however, the percolated domains and their connectivity in the optical images made identification of the phases difficult.…”
Section: Resultsmentioning
confidence: 79%
“…While the exact size and shape of domains in our SLB studies of this lipid mixture was difficult to control between experiments, the same general membrane morphology (two-phase co-existence, domains in registry) was consistent. The fluorescent probe DiI-C 20 has been shown to preferentially partition into solid-ordered (S o ) gel and L o membrane phases (Baumgart et al, 2007;Feigenson and Buboltz, 2001;Hao et al, 2001;Heberle et al, 2005;Korlach et al, 1999;Spink et al, 1990). Indeed, we observed that the probe showed a preference for one of the membrane phases; however, the percolated domains and their connectivity in the optical images made identification of the phases difficult.…”
Section: Resultsmentioning
confidence: 79%
“…Such terms as membrane fluidity and rigidity may be obsolete as they ambiguously mask complex lipid behavior and basically reflect high cholesterol content. For example, fluorescent and spin labels are often excluded from the ordered domains, as seen in fluorescent microscopy and through the self quenching of probes on the verge of the transition 18,37,38 . Exclusion of fluorescent groups and spin labels from solid ordered domains may under-report their presence in biological membranes.…”
Section: Discussionmentioning
confidence: 99%
“…DHE and Fast DiO were chosen as a FRET pair, at 1/100 and 1/700 fractions in total lipid. Light scattering and fluorescence background were controlled as described previously (71,72). Lipids were mixed in chloroform to 120 nmol, and the organic solvent was replaced by buffer using rapid solvent exchange (RSE) (68) and then sealed GUV samples described here were prepared by gentle hydration (38,73).…”
mentioning
confidence: 99%